Telerreabilitação no Tratamento da Dor Lombar Crônica na Atenção Primária: relato de caso - Leles, Adriele Silva (2022)
Treatment of people with people with special needs should give the need to remain accessible, as well as seek a reduction of the chronic form as treatment and provide interventions in a way to all who can benefit, there is an interest in studying a program of care in the telerehabilitation model, to investigate the potential of this modality of intervention in a group of patients for the management of chronic low back pain (CLBP) in primary care. This case report aimed to describe the use of telerehabilitation through the description of the implementation of an exercise-based treatment protocol, trained physical activity neurophysiology education, adapted for an unsupported online intervention of patients with CLBP. Male patient, 23 years old, student, single, resident of Fortaleza-CE, with chronic low back pain for 2 years. (END and Automation Scale for Chronic Pain as well), and for this last assessment it was Patient from Patient collection. The patient participated in a home exercise program using the video conferencing app for 6 weeks. Post-excellent results for the best designs across all instruments, as well as patient compliance and satisfaction. The positive results that this approach may be useful for improving long-term with patients, but requires more research as to the design of the intervention.